A brief exercise in currere and bathroom bills. Issue 3 (2nd September 2018) - Suarez, Mario I.; Lai Hing, Ebony; Slattery, Patrick
Abstract: North Carolina voted into law legislation known as the Privacy Facilities and Security Act, commonly known as HB2 or the anti-transgender "bathroom bill." We use Pinar's (1975a, 1975b, 2012 ) currere methodology as a brief exercise in deconstructing this bathroom bill and others similar to it. In this short piece, we go through each moment: the regressive, progressive, analytical, and synthetical. Historical, social, and biological aspects of the bill are discussed and critically analyzed to outline a pathway to a synthetical moment that includes cultural reconceptualization, social justice, and equality for disenfranchised groups such as transgender, intersex, and gender nonconforming people.